Corporate social policy and the ways of its realization - S. A. Shapiro (Путеводитель предпринимателя)
The article discusses corporate social policy as an important area of social responsibility on the example of the giant domestic steel industry - the company «Russian Aluminium». Considered a corporate «Policy», which defines the basic principles and main directions of development of the quality management system. Described aspects of corporate social policy and forms of socio-economic effect.